Performance of CREAM Calorimeter: Results of Beam Tests - Ahn, H S; Bagliesi, M G; Beatty, J J; Bigongiari, G; Castellina, A; Childers, J T; Conklin, N B; Coutu, S; Duvernois, M A; Ganel, O; Han, J H; Hyun, H J; et al. (2005)
The Cosmic Ray Energetics And Mass (CREAM), a balloon-borne experiment, is under preparation for a flight in Antarctica at the end of 2004. CREAM is planned to measure the energy spectrum and composition of cosmic rays directly at energies between 1 TeV and 1000 TeV. Incident particle energies will be measured by a transition radiation detector and a sampling calorimeter. The calorimeter was constructed at the University of Maryland and tested at CERN in 2003. Performance of the calorimeter during the beam tests is reported.